Mathematical modeling for digestible energy in animal feeds for tilapia - doi: 10.4025/actascianimsci.v34i3.13304 - Luiz Vítor Oliveira Vidal; Wilson Massamitu Furuya; Elias Nunes Martins; Tadeu Orlandi Xavier; Mariana Michelato; Thêmis Sakaguti Graciano (Acta Scientiarum. Animal Sciences, 2012)
The objective of this study was to formulate a mathematical model to estimate digestible energy in animal feeds for tilapia. Literature results were used of the proximate composition of crude protein, ether extract, mineral matter and gross energy, as well as digestible energy obtained in biological assays. The data were subjected to stepwise backward multiple linear regression. Path analysis was performed to measure the direct and indirect effects of each independent variable on the dependent one. To validate the model, data from independent studies and values obtained from a digestibility trial with juvenile Nile tilapia testing five meat and bone meals (MBM) were used, using the Guelph feces collecting system and chromium oxide (III) as an indicator. The obtained model is described below and cannot estimate digestible energy (DE) of animal origin: . The path coefficients were medium or low, the highest direct effect was from gross energy (0.529), while the highest indirect effect was from crude protein, through gross energy (0.439).